Analysis of the Distribution of Diarrhea Patients in Bogor Regency Month Using the Ordinary Kriging Method - Sitti Masyitah Meliyana R.; Ansari Saleh Ahmar (PT ARRUS Intelektual Indonesia, 2023)
Ordinary kriging is the most widely used kriging method. It serves to estimate a value at a point of a region for which a variogram is known, using data in the neighborhood of the estimation location. Ordinary kriging can also be used to estimate a block value. With local second-order stationarity, ordinary kriging implicitly evaluates the mean in a moving neighborhood. To see this, first a kriging estimate of the local mean is set up, then a simple kriging estimator using this kriged mean is examined. The objective of this study was to determine the pattern of diarrheal disease spread in Bogor Regency. The method according to the purpose of this research is Ordinary Kriging. To know the distribution of diarrhea disease in Bogor Regency by looking at the result of countour plot. Based on the countour plot, the area that has the highest number of diarrhea sufferers around Barekah and Bojonggenteng villages is marked with White contour color with the range of diarrhea sufferer is 40 - 43 people. Areas with the highest number of diarrheal diseases indicate that the area has a relationship with the number of diarrheal diseases in the surrounding area. Therefore, the area needs to be prioritized in improving water sanitation, counseling to the community and improving health services.